Quality work ethics and job satisfaction: An empirical analysis - Panigrahi, Shrikant; H. M., Al Nashash (Romanian Society for Quality Assurance - SRAC, 2019)
Quality is very crucial to understand how well an employee is doing. Quality of work shows how much an employee value them. Thus, this study examines the impact of strong quality work ethics on job satisfaction among banking employees in Jordan. There has been growing evidence supporting the association between quality work ethics and job satisfaction of employees. However, it is not clear why such association exists. This paper argues that in order to provide a clear understanding and convincing explanation of this association there is a need to improve the theoretical and analytical framework. Quantitative method with survey questionnaire was administered to collect information on quality work ethics and job satisfaction from 89 employees working in Jordanian banks. The finding of the study revealed that quality work ethics are positively associated with job satisfaction. These findings imply that quality work ethics is one of the key attributes to increase employee's job satisfaction together with other organizational outcomes. Most importantly, it is crucial for the managers to be aware that increasing employee's job satisfaction can lead to increased organizational commitment, lower labor turnover and improve productivity.